Peran Bahasa Indonesia dalam Pembentukan Karakter Generasi Alpha - Sri Puji Rahayu; Jumadi Jumadi; Dwi Wahyu Candra Dewi (Lembaga Pengembangan Kinerja Dosen, 2024)
This article discusses the importance of the role of Indonesian in the formation of the character of the alpha generation. In this era of technological and information advancement, everything can be obtained easily, including the alpha generation. Technology has an impact on the alpha generation from lifestyle, mindset, learning methods, even language. Indonesian for example, is second to the language that is developing out there to become a very serious problem. Therefore, the role of Indonesian in the formation of the character of the alpha generation is very much needed. The role of this language not only forms the character of the alpha generation, but also contributes to the development of society and the nation. The research conducted by the author uses a qualitative method, namely focusing on library studies through literature books and previous journals.